Myco-Facilitated Biosynthesis of Nano-Silver From Wasp Nest Fungus, Paecilomyces variotii, and Its Antimicrobial Activity Against MTCC Strains - Nayak, B. K.; Prabhakar, V.; Nanda, Anima (Frontiers in Microbiology, 2022)
Sunlight and dark assessed silver nanoparticles were synthesized from Wasp Nest fungus; Paecilomyces variotii at different pHs. Synthesized AgNPs under 6pH was found to be more prominent than 7 and 8 pHs. AgNPs were within 20-90nm range and polygonal with elongated in shape. FTIR spectra of light mediated AgNPs showed diverse transmittance bands than the silver nanoparticles synthesized during dark. The synthesized AgNPs were found with diverse antimicrobial activities against pathogenic MTCC bacterial strains i.e., Staph. aureus, Vibrio parahaemolyticus, E. coli, Shewanella putrefaciens and fungus; Candida albicans. Aqueous filtrate and filtrate mediated AgNPs combined with methanol solvent extract of YEMB had more inhibitory effects on all bacteria and Candida albicans. Further the combined effect of AgNPs and methanol solvent extract of YEMB culture filtrate found more effective against on E. coli while AgNPs combined with methanol solvent of aqueous filtrate had inhibitory effects on E. coli and Candida albicans.